Penilaian Performa Pemasok dalam Rantai Pasokan dengan Metode Sistem Inferensi Kabur pada PT. Mandar Utama Tiga Communications - , BAGAS TULUS WIBOWO, Drs. Pangestu Subagyo, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In nowadays printing and publishing business emulation, most companies confirmed that the key to survive in a competitive environment market is to generate substansial profit from operating low cost business. Most companies decided to form a partnership with their supplier to achieve high quality resources at optimum level of cost. In order to form a strategic partnership with the supplier, supplier development is considered to be a need. Supplier development can be achieved by supplier performance assessment. Fuzzy Inference System method is one of the supplier performance assessment approach. Supplier performance assessment with Fuzzy Inference System method consist of three main process, fuzzification, inference system, and defuzzification. This research is conducted in PT. Mandar Utama Tiga Communications, a printing and publishing manufacturer, with the purpose to assess supplier performance. Three aspects exist in assessing supplier performance, which is price, delivery, and quality. Based on the research and data analysis using Fuzzy Inference System, weighting rates based for price factor is at 38, delivery at 32, and quality at 30. Supplier performance assessment with Fuzzy Inference System method will generate performance score for each supplier based on their material supplies to the company. The supplier performance assesment recommends that the company should choose its supplier based on their highest performance score for future partnership purpose. For paper supplies, the researcher recommends Mitra Abadi. For chemical supplies, the researcher recommends Nagasaki. For laminating supplies, the researcher recommends CMS. For outdoor printing supplies, the researcher recommends Djogja Printing.